Strafrechtliche Verfolgung von Tierschutzkriminalität in der Landwirtschaft Eine empirische Untersuchung - Hahn, Johanna; Hoven, Elisa (Das Recht der Tiere und der Landwirtschaft, 2022)
This book addresses the realities of criminal prosecution of animal cruelty crimes in the agriculture. On the basis of investigation files and expert interviews the authors examine how the current laws are applied by veterinary authorities, public prosecutors and the courts. It becomes clear that the existing criminal offences do not do justice to the realities of modern farm animal use. Based on the empirical results, the authors develop reform proposals on a substantive, procedural and institutional level for an appropriate and effective punishment of animal cruelty crimes. The work serves as a guidance for both legislators and law enforcement agencies.